Aquinas on the Limited Authority of Erroneous Conscience - Pidel, Aaron 1978- (2025)
Some theologians, beginning with Karl Rahner, have claimed a Thomistic pedigree for the idea that acts occasioned by an erring conscience can be morally good, even when said acts contradict known ecclesial clarifications of the natural law. But this construes the authority of erring conscience in a way foreign to Aquinas's thought, isolating the act of conscience from the regulating habits of synderesis and prudence. There are good reasons, moreover, for preferring Aquinas's understanding of conscience to the revisionist interpretation.
Keywords: Conscience; Dissent; Ignorance; Natural Law; Prudence; Karl Rahner; Synderesis; Thomas Aquinas